Sonographic criteria for the evaluation of dietary compliance of children with celiac disease (Annals of Medical Research, 2021)
Aim: Although the only known way to avoid complications like iron deficiency anemia, short stature in celiac disease is a strict gluten-free diet, it is a known fact that not all patients follow the diet. Diet compliance is practically evaluated with serum antibodies, such as tissue transglutaminase antibody. The aim of this study was to evaluate the contribution of less invasive ultrasound and Doppler ultrasound in evaluating dietary compliance in celiac patients.Materials and Methods: Twenty-five male and 47 female cases aged five to 17 years were included in the study. Seventy-two patients diagnosed with celiac disease and followed up were divided into two groups according to dietary compliance based on the results of tissue transglutaminase IgA antibody. Pericardial fluid, hepatosteatosis, mesenteric lymphadenopathy, intraabdominal free fluid, small intestine diameter, small intestine wall thickness and gallbladder volume, superior mesenteric artery (SMA) diameter, portal vein diameter, SMA peak systolic velocity, and portal vein velocity were measured on ultrasound. The differences between the groups were statistically compared.Results: The frequency of mesenteric lymphadenopathy, superior mesenteric artery diameter, SMA peak systolic velocity, and portal vein velocity were increased in children who did not follow the recommended diet. There was no significant difference between the groups in terms of hyperperistalsis, gallbladder volume, and portal vein diameter. Pericardial fluid, fatty liver, small intestine dilatation, and increased intestinal wall thickness were not detected in either group.Conclusion: Ultrasound can play an important role in the follow up of children with celiac disease. It can provide clinicians with an insight into the dietary compliance of these cases.
Keywords: Celiac disease; gluten-free diet; superior mesenteric artery; ultrasound